2015
DOI: 10.1038/mp.2015.125
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation in CRHR1 predisposes to panic disorder: evidence for biased fear processing

Abstract: Corticotropin releasing hormone (CRH) is a major regulator of the hypothalamicpituitary-adrenal (HPA) axis. Binding to its receptor CRHR1 triggers the downstream release of cortisol, a hormone needed for regulation of stress responses. Biochemical, behavioral and genetic studies revealed CRHR1 as a possible candidate gene for mood and anxiety disorders. Here, we aimed to evaluate CRHR1 as a candidate molecule in panic disorder (PD).Allelic variation throughout the CRHR1 gene was captured by 9 selected single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 74 publications
4
38
0
Order By: Relevance
“…31 CRHR1 encodes a G protein-coupled receptor for neuropeptides involved in diverse physiological processes including stress and immune responses. 32 Overall, these data strongly suggest that the H1 MAPT -haplotype contributes to increased risk for FTD and PD and its effect is likely mediated by modulating changes in the expression profiles of functionally important cis -genes.…”
Section: Discussionmentioning
confidence: 69%
“…31 CRHR1 encodes a G protein-coupled receptor for neuropeptides involved in diverse physiological processes including stress and immune responses. 32 Overall, these data strongly suggest that the H1 MAPT -haplotype contributes to increased risk for FTD and PD and its effect is likely mediated by modulating changes in the expression profiles of functionally important cis -genes.…”
Section: Discussionmentioning
confidence: 69%
“…Genetic studies have established that loss of Crhr1 in glutamatergic cells in the cerebral cortex is anxiolytic (Refojo et al, 2011), and that CRH dysfunction can contribute to human anxiety related disorders (Weber et al, 2015; Smoller, 2016). Although no data suggesting an interaction of the OXT/OXTR and CRH/CRHR1 systems in the cerebral cortex has been reported previously, the specific and high expression of Crhbp in OxtrINs suggested to us that the anxiogenic effects of CRH on layer 2/3 pyramidal cells might be modulated by release of CRHBP from OxtrINs, and that differential sensitivity of this system may account for the male specific anxiolytic effects of OxtrINs activation.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical and clinical studies have indicated that CRHR1 is a possible candidate gene for mood and anxiety disorders[79,125,126]. Weber et al[127] studied different variants located within the CRHR1 gene with regard to possible associations with PD. Genotyping in 531 matched case/control pairs (PD patients and healthy control subjects) revealed 9 single nucleotide polymorphisms (SNPs).…”
Section: Resultsmentioning
confidence: 99%
“…The risk allele carriers showed aberrant fear conditioning predominantly in the bilateral prefrontal cortex and altered safety signal processing in the amygdala, suggesting existing fear sensitization and sustained fear. Furthermore, in this multilevel study, Weber et al[127] performed an expression analysis of CRHR1 gene. For this purpose, postmortem tissue of 76 deceased individuals obtained from the MRC Sudden Death Brain and Tissue Bank, Edinburgh, United Kingdom, was analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation